Nanotechnology - the Future Dental Specialization - Kumar, Santhosh; G, Pratibha; Nigam, Akshay (International Journal of Engineering and Technology, 2018)
Nanoscience can be designed to suit the needs of the people and the technology driven by this technology has the potential to improve the state of the developing world. Nanotechnology driven mechanics will become a reality once it is affordable and is accessible to every clinician. Microscale robots that are programmable and controllable allows humans to execute at the cellular and subcellular levels. The application of nanomaterials in dentistry has extended from nano-drug delivery to precision dentistry. With the demand for precision in dentistry, the nanomaterials have been a boon for the upcoming dentists. Nanomaterials have provided better strength, adhesion, resistance to decay, increases life and provides excellent color match in dental restorations. They have furnished better material property for regenerative materials used as bone substitutes.Nanomaterials have also been used for diagnosis of oral pathologies and have provided surgical precision instruments. However, there are drawbacks to its use; that it can produce nanowastes that can accumulate and can result in unwanted environmental hazards. However, with the emerging need for future useful technology, this branch is gaining popularity and can overcome the problems and can provide a better future.Â Â Â